Clinicopathologic Characteristics and Outcomes of Massive Multinodular Goiter: A Retrospective Cohort Study - Chen, Qiang; Su, Anping; Zou, Xiuhe; Liu, Feng; Gong, Rixiang; Zhu, Jingqiang; Li, Zhihui; Wei, Tao (Frontiers in Endocrinology, 2022)
Background Thyroidectomy for massive goiters is challenging because of the increased risk of tracheomalacia, combined sternotomy, postoperative morbidity, and mortality, whereas studies investigating the clinicopathologic characteristics, postoperative morbidities, and surgical outcomes of massive goiters are limited. Methods Patients with goiters undergoing thyroid surgery between 2009 and 2019 were retrospectively reviewed. A total of 227 patients were enrolled and divided into massive goiter group and large goiter group according to the weight of the goiter. Clinicopathologic characteristics, postoperative morbidities, and surgical outcomes were compared between the two groups. Results Seventy-four patients (32.6%) had a goiter weighing more than 250 g and 153 patients (67.4%) were categorized in the large goiter group. Compared to large goiter patients, massive goiter patients had higher rates of retrosternal extension (82.4% vs. 30.7%), combined sternotomy (12.2% vs. 1.3%), intensive care unit admission (25.7% vs. 7.2%), transient hypoparathyroidism (41.9% vs. 25.5%), and transient recurrent laryngeal nerve palsy (10.8% vs. 3.3%) as well as prolonged length of hospital stay (P < 0.05). Conclusions Massive goiter patients were at increased risk of combined sternotomy, intensive care unit admission, postoperative morbidities as well as prolonged length of hospital stay after thyroidectomy compared to large goiter patients, but most of them can be treated through a cervical approach with a favorable outcome.